Pathophysiological Role of Histamine H4 Receptor in Cancer: Therapeutic Implications - Nicoud, Melisa B.; Formoso, Karina; Medina, Vanina A. (Frontiers in Pharmacology, 2019)
Cancer is a leading cause of death in both developed and developing countries. Although advances in cancer research lead to improved anti-neoplastic therapies, they continue to have unfavorable outcomes, including poor response and severe toxicity. Thus, the challenge for the new therapeutic approaches is to increase anti-tumor efficacy by targeting different molecules encompassed in the tumor and its microenvironment, as well as their specific interactions. The histamine H4 receptor (H4R) is the last discovered histamine receptor subtype and it modulates important immune functions in innate and in adaptive immune responses. Several ligands have been developed and some of them are being used in clinical trials for immune disorders with promising results. When searched in The Cancer Genome Atlas (TCGA) database, human H4R gene was found to be expressed in bladder cancer, kidney cancer, breast cancer, gastrointestinal cancers, lung cancer, endometrial cancer, and skin cancer. In the present work, we aimed to briefly summarize current knowledge in H4R´s pharmacology and in the clinical use of H4R ligands before focusing on recent data reporting the expression of H4R and its pathophysiological role in cancer, representing a potential molecular target for cancer therapeutics. H4R gene and protein expression in different types of cancers compared with normal tissue as well as its relationship with patient prognosis in terms of survival will be described.